Upaya Meningkatkan Pengetahuan Sains Melalui Pendekatan Eksplorasi Lingkungan Sekitar di TK Putra I Kota Jambi Kelompok B Tahun Ajaran 2016/2017 - Delima Delima (Universitas Batanghari Jambi, 2019)
This study aims to improve the knowledge of Putra I Kota Jambi Kindergarten students in their scientific knowledge through methods or approaches to the exploration of the surrounding environment. The research was conducted by class action with quantitative and qualitative methods. The research subject was a student of Putra I TK Jambi City Group B consisting of 19 children. The data analysis technique used is descriptive percentative and descriptive of student activities. Data validity uses content validity. The results of the study showed that the Exploration of the Surrounding Environment can improve students' scientific abilities as evidenced by the fact that the initial conditions prior to the action, the average percentage of children's scientific ability was 31%. Then after the classroom action research was carried out through Environmental Exploration, the average percentage of children's scientific ability increased to 41%. Next in the second cycle the average percentage of children's scientific abilities increased by 59% and the last in the third cycle the average percentage of children's scientific ability had reached the target in accordance with what was expected by the researchers, amounting to 83%. Suitability for the use of learning methods will determine the achievement of educational goals. All educational goals that want to be achieved should have been arranged in the curriculum as a tool that must be owned by the teacher in carrying out their duties. While how to use the tool will depend on the competence of the teacher. The ability of the teacher to connect the goals of education by achieving it cannot be separated from three important steps. These three important steps include planning, implementation and evaluation. Determination of learning methods occurs in three processes of these important steps. Determination of the method of exploration of the surrounding environment to improve science knowledge is the right way and proven successful in the practice of Classroom Action Research in Putra I TK Jambi City.